Azo dyes degradation and mutagenicity evaluation with a combination of microbiological and oxidative discoloration treatments - Rodrigues de Almeida, Erica Janaina; Christofoletti Mazzeo, Dânia Elisa [UNESP]; Deroldo Sommaggio, Lais Roberta [UNESP]; Marin-Morales, Maria Aparecida [UNESP]; Rodrigues de Andrade, Adalgisa [UNESP]; Corso, Carlos Renato [UNESP] (My University, 2019)
This work evaluated the degradation of the Acid Blue 161 and Procion Red MX-5B dyes in a binary solution by the filamentous fungus Aspergillus terreus and the yeast Saccharomyces cerevisiae in systems with and without electrochemical oxidation as the pretreatment process. UV–Vis spectrophotometry, high-performance liquid chromatography with (HPLC), Fourier transform infrared (FT-IR) spectroscopy and Salmonella/microsome assay (Ames test) were applied towards the degradation analysis of the dyes. Adsorption tests with white clay immobilized on alginate were also conducted after the discoloration treatments to remove intermediate metabolites formed during the degradation of the dye molecules. The discoloration treatments led to the complete color removal of the solutions in all the systems tested. The clay demonstrated affinity for the metabolites formed after discoloration treatments, the removal rates were variable, but the all systems has proved efficient. The Salmonella/microsome assay (Ames test) with strains TA98 and TA100 in the absence and presence of exogenous metabolism (S9 microsomal system, Moltox) revealed that the initial molecules and by-products of the metabolism of the dyes were direct mutagens. The electrochemical/A. terreus/clay system was able to discolor the solutions and transform the direct mutagens into non-mutagenic compounds in addition to reducing the mutagenic potency of the pro-mutagens to the Salmonella strain TA100/S9, which demonstrates the high efficiency of this system with regard to discoloring and degrading azo dye molecules and their by-products. Therefore, this study showed that although not having standard treatment system for this type of pollutant, the combination of treatments can be considered promising. The use of electrochemical oxidation along with microbiological treatment may lead to the degradation and mineralization of these compounds, reducing or eliminating the environmental impact caused by the improper disposal of these dyes in aquatic environments.
Keywords: Azo dyes; Electrochemical treatments; Microbiological treatments; Salmonella/microsome assay; Wastewater treatment